RISIKO KEMATIAN SELAMA PERAWATAN DI RUMAH SAKIT PENDERITA INFARK MIOKARD AKUT DENGAN ELEVASI SEGMEN ST (IMAâEST) YANG DILAKUKAN TERAPI FIBRINOLITIK DIBANDING INTERVENSI KORONER PERKUTAN (IKP) PRIMER - , Irsad Andi Arso, dr, Prof. Dr. Bambang Irawan SpPD., KKV., SpJP (K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: A study comparing fibrinolityc therapy and primary percutaneouscoronary intervention (PCI) in patients with STEMI has been reported in developed countries. Only few studies reporting the outcome of pirmary PCI in developing countries where this intervention had just routinely performed in the last 3 years. Objective: To observed the cardiovascular mortality in patients with STEMI who received fibrinolytic therapy compared with primary PCI during hospitalization. Methodology and Methods: we performed retrospective cohort study using medical record of STEMI patients with the onset <12 hours who received fibrinolytic therapy and primary PCI at Dr. Sardjito Hospital at Yogyakarta starting January 1st, 2008 until March 31st, 2010. Clinical outcomes: Primar outcomes was cardiovascular mortality and secondary outcomes were heart failure, post-infarction angina pectoris, and side effects of bleeding. Results: In 78 patients who received fibrinolityc therapy and 53 patients with primary PCI we found that cardiovascular mortality was not significantly different (6.4% vs 7.5%